Edukasi Media sebagai Alat Sosialisasi Kesetaraan Gender di Wilayah Kelurahan Pondok Labu Jakarta Selatan - Wardani, Ayu; Hayati, Kumala; Saraswati, Dini Putri; Intyaswati, Drina (MAYARA: Jurnal Pengabdian Masyarakat, 2025)
In Indonesia, issues related to gender equality remain a significant challenge, ranging from the topic of double roles and emancipation to sexual violence and patriarchal culture. Therefore, the media is needed as a tool to disseminate the importance of gender equality, both through conventional and digital media. The importance of education on gender equality can begin with small community groups, such as elderly groups, Family Welfare Empowerment groups, and other social activist communities involved in local empowerment programs. This community engagement program was carried out at RPTRA in Pondok Labu Subdistrict, South Jakarta. The participants in this activity included administrators from the Pondok Labu subdistrict, the Family Welfare Empowerment group (PKK), and the Elderly Learning Center, totaling 25 participants. The method used was a lecture delivered by the speaker (a lecturer from the Faculty of Social and Political Sciences, UPN Veteran Jakarta), followed by a question-and-answer discussion session. The aim of this activity was to provide knowledge regarding the importance of gender equality and the role of the media as a tool for promoting gender equality